Nodular Scleritis Revealing Metastasis of Breast Cancer: Diagnosis Not to Be Neglected - Belghmaidi Sarah; Ghazza Ahmed; Boutgayout Saloua; Hajji Ibtissam; Moutaouakil Abdeljalil; Dref Maria; Fakhri Anass; Raiss Hanane (Case Reports in Ophthalmological Medicine)
We report the case of ocular metastasis in a 48-year-old woman presenting left eye redness and pain. The patient was followed in another health institution for nodular scleritis and received systemic corticosteroids with moderate improvement. Medical history revealed that she was diagnosed three years ago with invasive ductal carcinoma of the left breast treated by tumorectomy with ganglion dissection. An ophthalmological examination found a hard scleral nodule with vascular architectural disorganization. A biopsy was performed, and the histopathological study revealed the presence of secondary tumor proliferation of poorly differentiated carcinoma of mammary cancer. This case report shows the fact that any unusual ocular presentation, even one simulating anterior scleritis, in a patient with a history of breast cancer should raise suspicion of metastasis.